Black International Student Lives Matter - Mwangi, Chrystal A. George (International Higher Education, 2020)
International students who are racially Black contend with racist-nativism in US society and in their US colleges and universities. This article highlights how Black international students navigate the intersection of their race and nativity in US higher education. It offers considerations as well as demands for US higher education institutions to demonstrate that Black international students’ lives matter.